PENGARUH KOMPETENSI PEGAWAI, INSENTIF DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA YANG BERDAMPAK PADA KINERJA APARATUR SIPIL NEGARA (ASN) RSUD dr. H. KOESNADI BONDOWOSO - Rahmawati, Rahmawati; Pramesthi, Riska Ayu; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The aim of this research is to determine and analyze the influence of competence, incentives, work environment on the performance of ASN RSUD dr. H. Koesnadi Bondowoso with satisfaction as an intervening variable. The research was conducted from February to June 2024. The population consisted of all ASN RSUD dr. H. Koesnadi Bondowoso, totaling 516 employees. With a total sample of 84 respondents. The sampling method uses nonprobability sampling with purposive sampling technique. Researchers used Structural Equation Model - Partial Least Square (PLS-SEM) to analyze data and test hypotheses in this research. The results of the research show that competence, incentives and work environment have a significant positive effect on job satisfaction of ASN RSUD dr. H. Koesnadi Bondowoso. Competence and job satisfaction have a significant positive effect on the performance of ASN RSUD dr. H. Koesnadi Bondowoso. Meanwhile, incentives have a negative and insignificant effect on the performance of ASN RSUD dr. H. Koesnadi Bondowoso and the work environment have a positive but not significant effect on ASN performance at RSUD dr. H. Koesnadi Bondowoso. Indirectly, employee competency and work environment affect the performance of ASN RSUD dr. H. Koesnadi Bondowoso through job satisfaction has a significant positive effect, while incentives on ASN performance through job satisfaction have a positive but not significant effect.